Uso de componentes naturales encapsulados como aditivos antimicrobianos en empaque de alimentos - Flores Ramirez, Regina (2022)
Microbial action is one of the main causes of food decomposition, causing concern, not only in the area of public health but also in the industry, since it generates large economic losses. This is why packaging is one of the main measures or strategies used to protect products; however, the most used material for this purpose is plastic, which after fulfilling its function is discarded, becoming a serious environmental problem. Therefore, in recent years, edible packaging made from food-grade biopolymers has attracted attention because, in addition to being friendly to the environment, they also allow the incorporation of antimicrobial substances or preservatives, which help to extent the shelf life of food products. To date, nitrites and benzoates have been used as food preservatives; however, they have raised concerns due to the allergic reactions they can cause and the possible formation of toxic metabolites. That is why, lately, the interest in substances with microbial activity of natural origin has been increasing, among them we have phenolic compounds, which abundantly distributed in plants. Nevertheless, their disadvantage is that they are sensitive to various environmental factors, so microencapsulation is an alternative to promote the protection and stability of these sensitive compounds.